2022
DOI: 10.3389/fnins.2022.925698
|View full text |Cite
|
Sign up to set email alerts
|

The cumulative therapeutic effect of acupuncture in patients with migraine without aura: Evidence from dynamic alterations of intrinsic brain activity and effective connectivity

Abstract: We explored the dynamic alterations of intrinsic brain activity and effective connectivity after acupuncture treatment to investigate the underlying neurological mechanism of acupuncture treatment in patients with migraine without aura (MwoA). The Functional Magnetic Resonance Imaging (fMRI) scans were separately obtained at baseline, after the first and 12th acupuncture sessions in 40 patients with MwoA. Compared with the healthy controls (HCs), patients with MwoA mostly showed a decreased dynamic amplitude o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
4
0
1
Order By: Relevance
“…A few studies [ 52 , 53 , 57 , 58 ] explored whether acupuncture-related functional brain changes were associated with patients´ improvement after treatment, showing an association between changes in brain activity and changes in the severity and frequency of migraine attacks.…”
Section: Resultsmentioning
confidence: 99%
“…A few studies [ 52 , 53 , 57 , 58 ] explored whether acupuncture-related functional brain changes were associated with patients´ improvement after treatment, showing an association between changes in brain activity and changes in the severity and frequency of migraine attacks.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the neural mechanisms underlying VMI can help provide interventions for individuals with VMI difficulties. In addition, previous studies suggested that EC analysis can more accurately determine causal relationships between brain regions, and thus, measures how one brain region influences another in a specific direction, whereas unidirectional functional connectivity analysis only provides information on the correlation between brain regions [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“… 22–24 Chen et al showed that acupuncture might relieve migraine without aura (MwoA) by increasing the EC of superior lobe of left cerebellum, rostral ventromedial medulla, and right precuneus. 25 No investigations have been done to determine the direction of the altered connections, despite the possibility that the specific internal brain effective connectivity may potentially be affected after the EA intervention of KOA.…”
Section: Introductionmentioning
confidence: 99%